WS-5 Engaging consumers in the design of advance care planning services and resources. (1st September 2015) - Manson, Leigh; Muir, Shona; Sudore, Rebecca L
Abstract : Background: The New Zealand ACP programme has been co-designed in partnership with consumers resulting in services and resources that meet the needs of our community. We will share our experiences from this co-designed work and principles for creating patient-centred health education materials. Aim: By the end of the workshop participants will: Understand the importance of the consumer's voice in service development and design Learn how to create universally easy-to-understand print and web-based materials Learn about co-design and tools to incorporate into program development Explore how co-design could be used in participants' own organisation. Methods: Using an interactive workshop approach we will present the importance, challenges, and approaches to designing services and easy-to-understand materials that engage consumers and meet their cultural and health literacy needs. We will then present the process of co-design and how to work with consumers as equal partners in the design and delivery of ACP. Specific examples from New Zealand's ACP programme will be used to highlight benefits and challenges. Then, working in small groups participants will learn how to: (1) define the problems/opportunities within their community, (2) engage consumers, and (3) select the most appropriate co-design tools for their programs. Discussion: Co-design coupled with easy-to-understand health materials can engage communities in ACP. Throughout this interactive workshop participants will have an opportunity to discuss their individual programs and ask questions. Conclusion: Co-design effectively supports consumers and healthcare professionals to work together to design services that improve the experience for both the service providers and service users.